Note: Determine whether the solution to the new equation is a solution to the old system of equations by graphing. Use Desmos!
(1 point)
The solution to the original system of equations (is also, is not) a solution to the new equation.
Solve the system of equations by SUBSTITUTION.
6y + 5x = 8
x + 3y = -
What would your equation look like after the first substitution? (6y + 5(3y - 7) = 8, 6y + 5(- 3y - 7) = 8, 6(- 3y - 7) + 5x = 8, 6(3y + 8) + 5x = - 7)
1 answer
The correct equation after the first substitution would be 6y + 5(- 3y - 7) = 8.